Meeting the Challenge of Drought through Soil and Water Conservation - Bali, J.S. (Journal of Soil and Water Conservation, 2022)
The 1987 drought is considered as the worst that the country has experienced in about a century and a quarter. The glaring facts of the drought, namely (1) they are not new, (ii) the drought troubles are most where poverty is most, (iii) urban consumerism and giganticism continue to consume bulk of the national resources, (iv) relief expenditure, and (v) absence of effective long term integrated plann- ing, have been discussed. Past soil conservation measures in the context of drought have been described and new tools for meeting the challenges have been outlined. They include watershed management, zero runoff farming, creation of the department of watershed management and ag•o-industrial water- sheds.